IMPLEMENTATION OF VALUE STREAM MAPPING TO REDUCE WASTE IN WARRANTY CLAIM PROCESS AT COMMERCIAL VEHICLE AUTOMOTIVE COMPANY - Sokheh Nur Maulana; Uly Amrina (Journal of Industrial Engineering Management, 2022)
In the automotive industry, after-sales service becomes one of the marketing strategies used. The obstacles arose when there was a problem with the products, but the services related follow-up decisions problem report from customers seems too long because the information delivered by the dealer has not been fulfilled. This research aims to identify waste and implement improvements that can reach the standard after-sales service time set by the company. This study uses the value stream mapping (VSM) method combined with a root cause analysis approach to reduce waste. The problem identification found that the most prolonged decision was the starting system. Then, the dominant waste is a waiting process. The VSM improved processing time efficiency by 34.47% or 33.97 hours (1.4 days). This result proved that the overall reporting time reached 60 hours (2 days) as the company target.